Zinc alleviates cadmium toxicity by modulating photosynthesis, ROS homeostasis, and cation flux kinetics in rice. (October 2020) - Adil, Muhammad Faheem; Sehar, Shafaque; Han, Zhigang; Wa Lwalaba, Jonas Lwalaba; Jilani, Ghulam; Zeng, Fanrong; Chen, Zhong-Hua; Shamsi, Imran Haider
Abstract: Understanding of cadmium (Cd) uptake mechanism and development of lower Cd crop genotypes are crucial for combating its phytotoxicity and meeting 70% increase in food demand by 2050. Bio-accumulation of Cd continuously challenges quality of life specifically in regions without adequate environmental planning. Here, we investigated the mechanisms operating in Cd tolerance of two rice genotypes (Heizhan-43 and Yinni-801). Damage to chlorophyll contents and PSII, histochemical staining and quantification of reactive oxygen species (ROS), cell viability and osmolyte accumulation were studied to decipher the interactions between Cd and zinc (Zn) by applying two Cd and two Zn levels (alone as well as combined). Cd 2+ and Ca 2+ fluxes were also measured by employing sole Cd100 (100 μmol L −1 ) and Zn50 (50 μmol L −1 ), and their combination with microelectrode ion flux estimation (MIFE) technique. Cd toxicity substantially reduced chlorophyll contents and maximal photochemical efficiency (Fv /Fm ) compared to control plants. Zn supplementation reverted the Cd-induced toxicity by augmenting osmoprotectants and interfering with ROS homeostasis under combined treatments, particularly in Yinni-801 genotype. Fluorescence microscopy indicated a unique pattern of live and dead root cells, depicting more damage with Cd10, Cd15 and Cd15 +Zn50 . Our results confer that Cd 2+ impairs the uptake of Ca 2+ whereas, Zn not only competes with Cd 2+ but also Ca 2+, thereby modifying ion homeostasis in rice plants. This study suggests that exogenous application of Zn is beneficial for rice plants in ameliorating Cd toxicity in a genotype and dose dependent manner by minimizing ROS generation and suppressing collective oxidative damage. The observations confer that Yinni-801 performed better than Heizhan-43 genotype mainly under combined Zn treatments with low-Cd, presenting Zn fortification as a solution to increase rice production. Graphical abstract: Image 1 Highlights: Zn alleviated Cd toxicity in a dose- and genotype-dependent manner. Root mature zone Cd 2+ and Ca 2+ flux kinetics differed in response to Cd–Zn in rice. The entrance of Cd into root cells occurs by utilizing Ca pathway. Cd–Zn interaction at high dosage has antagonistic effects on rice.